2015
DOI: 10.3109/0167482x.2015.1074173
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endometriosis on quality of life and mental health: pelvic pain makes the difference

Abstract: Pain significantly affects women's experience of endometriosis. The medical treatment of endometriosis with pain may not be sufficient and psychological intervention is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
268
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 327 publications
(290 citation statements)
references
References 41 publications
11
268
2
9
Order By: Relevance
“…For example, no studies have systematically investigated how and why endometriosis differently affects women, such that not all of them are distressed. It is known that women with painful endometriosis may have poorer mental health and quality of life as compared with those who do not have pain (Facchin et al 2015;Pope et al 2015). However, more research is needed to develop a comprehensive explanatory theory of the psychological impact of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, no studies have systematically investigated how and why endometriosis differently affects women, such that not all of them are distressed. It is known that women with painful endometriosis may have poorer mental health and quality of life as compared with those who do not have pain (Facchin et al 2015;Pope et al 2015). However, more research is needed to develop a comprehensive explanatory theory of the psychological impact of endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Endometriosis is painful in most women (up to 80%; Bulletti et al 2010), who may experience different types of pain, such as dysmenorrhea (pain at menstruation), dyspareunia (pain at intercourse), dyschezia (pain at defecation), and chronic pelvic pain. Painful endometriosis is associated with depression, anxiety, and impaired quality of life (Facchin et al 2015;Pope et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As a chronic gynecological condition often associated with pelvic pain -either cyclic and temporary (such as dysmenorrhea, dyspareunia, and dyschezia), or chronic [1,2] -endometriosis negatively affects women's quality of life and psychological health [3][4][5]. Painful endometriosis involves remarkable limitations in everyday activities, including education and work [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Facchin et al (2015) found that women with pelvic pain and endometriosis had poorer quality of life and more depression than other women. Women often feel isolated and can lack support socially from friends and family who may just perceive that they have 'period pain'.…”
Section: Impact On Women's Lives (Physical Psychological Social Rementioning
confidence: 99%